A robust walking detection algorithm using a single foot-worn inertial sensor: validation in real-life settings. - Prigent, Gaëlle; Aminian, Kamiar; Cereatti, Andrea; Salis, Francesca; Bonci, Tecla; Scott, Kirsty; Mazzà, Claudia; Alcock, Lisa; Del Din, Silvia; Gazit, Eran; Hansen, Clint; Paraschiv-Ionescu, Anisoara (Medical & Biological Engineering & Computing, 2023)
Walking activity and gait parameters are considered among the most relevant mobility-related parameters. Currently, gait assessments have been mainly analyzed in laboratory or hospital settings, which only partially reflect usual performance (i.e., real world behavior). In this study, we aim to validate a robust walking detection algorithm using a single foot-worn inertial measurement unit (IMU) in real-life settings. We used a challenging dataset including 18 individuals performing free-living activities. A multi-sensor wearable system including pressure insoles, multiple IMUs, and infrared distance sensors (INDIP) was used as reference. Accurate walking detection was obtained, with sensitivity and specificity of 98 and 91% respectively. As robust walking detection is needed for ambulatory monitoring to complete the processing pipeline from raw recorded data to walking/mobility outcomes, a validated algorithm would pave the way for assessing patient performance and gait quality in real-world conditions.
EVALuna2:561333